The feeling of history - Hirschkind, Charles. (Chicago, IL ; London)
206 sayfa
Keywords: “In today’s world, the lines between Europe and the Middle East, between Christian Europeans and Muslim immigrants in their midst, seem to be hardening. Alarmist editorials compare the arrival of Muslim refugees with the “Muslim conquest of 711,” warning that Europe will be called on to defend its borders. Violence and paranoia are alive and well in Fortress Europe. Against this xenophobic tendency, The Feeling of History examines the idea of Andalucismo—a modern tradition founded on the principle that contemporary Andalusia is connected in vitally important ways with medieval Islamic Iberia. Charles Hirschkind explores the works and lives of writers, thinkers, poets, artists, and activists, and he shows how, taken together, they constitute an Andalusian sensorium. Hirschkind also carefully traces the various itineraries of Andalucismo, from colonial and anticolonial efforts to contemporary movements supporting immigrant rights. The Feeling of History offers a nuanced view into the way people experience their own past, while also bearing witness to a philosophy of engaging the Middle East that experiments with alternative futures“ --